2019
DOI: 10.1111/abac.12151
|View full text |Cite
|
Sign up to set email alerts
|

Equity Financial Assets: A Tool for Earnings Management—A Case Study of a Chinese Corporation

Abstract: With China's adoption of principles-based international accounting standards and its convergence with International Accounting Standard 39 (IAS 39), Chinese companies have discretion under the original Accounting Standards for Enterprises 22 (CAS 22) as to how they account for the initial measurement, sale, and subsequent reclassification of financial assets. We use a Chinese company ('Company A') as a case study to illustrate how earnings are managed to exploit this discretion. We document that the company re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…It could also be noted that differentiating between short-and long-term investments may foster opportunistic behavior and classificatory manipulation (Guo et al, 2019). Effective corporate governance is therefore crucial in such a context.…”
Section: Classification Criteria For a New Asset Class Of Long-term Equity Investmentsmentioning
confidence: 99%
“…It could also be noted that differentiating between short-and long-term investments may foster opportunistic behavior and classificatory manipulation (Guo et al, 2019). Effective corporate governance is therefore crucial in such a context.…”
Section: Classification Criteria For a New Asset Class Of Long-term Equity Investmentsmentioning
confidence: 99%
“…It is evident from current study by (Mellado & Saona, 2019) who found that institutional investment and effective regulatory system reduces REM. (Guo, Lu, Ronen, & Ye, 2019) found further that stable and long term sighted institutional investment reduces cost of equity. Foreign institutional investors plays significant role in curtailing EM practices specially in firms, where monitoring is more valuable (Lel, 2019).…”
Section: Recommendationsmentioning
confidence: 88%
“…Guo et al. (2019) show that firms reclassify their AFS equity investments as long term to decrease the volatility in their reported profits. Khan and Bradbury (2014) find that OCI displays higher volatility relative to net income, but this higher volatility has no association with higher market risk (the market does not price the volatility).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%